Research on the effect of post-activation potentiation under different velocity loss thresholds on boxer’s punching ability - Cui, Weijia; Chen, Yiming; Wang, Dexin (Frontiers in Physiology, 2024)
This study was conducted in accordance with the principles of velocity-based training theory, with the objective of investigating the effects of post-activation potentiation (PAP) induced by different velocity loss (VL) thresholds (10% vs. 20%) on the punching ability of boxers. In addition, the aim was to determine the velocity loss thresholds and time nodes that produced the optimal activation effect. Twenty-four male elite boxers were randomly assigned to three groups: CON, 10 VL, and 20 VL. All subjects in the three groups underwent an activation intervention involving an 85% of the one-repetition maximum (1RM) squat, with 6-8 repetitions performed in the CON. The number of repetitions in the 20%VL and 10 VL was determined based on the velocity loss monitored by the GymAware PowerTool system. Four time points were selected for observation: the 4th, 8th, 12th and 16th minutes. These were chosen to test the subjects’ punching ability. The results demonstrated that activation training at different VL induced a post-activation potentiation in boxers, improving punching ability bilaterally and to a greater extent than in the CON. The dominant side demonstrated the greatest efficacy at the 12th minute under the 20% velocity loss threshold, while the non-dominant side exhibited the greatest efficacy at the 8th minute under the 10% velocity loss threshold.